2017
DOI: 10.1097/prs.0000000000002900
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Rat Skin Flap Model That Distinguishes between Venous Congestion and Arterial Ischemia: The Reverse U-Shaped Bipedicled Superficial Inferior Epigastric Artery and Venous System Flap

Abstract: The flap facilitated discrimination of the effects of ischemia and congestion. This new rat skin flap model is simple and easy to construct, and has a consistent flap survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…[1][2][3][4] By fully understanding the characteristics of the choke vessels and true anastomosis, the flap can be raised safely in most cases, but exceptions can happen. 8 The study of Matsumoto et al 10 showed that the choke vessels might not have equal flow carrying capabilities in the rat SIEA model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4] By fully understanding the characteristics of the choke vessels and true anastomosis, the flap can be raised safely in most cases, but exceptions can happen. 8 The study of Matsumoto et al 10 showed that the choke vessels might not have equal flow carrying capabilities in the rat SIEA model.…”
Section: Discussionmentioning
confidence: 99%
“…This paper claimed that ischemia or congestion happened after vessel ligation, and the distal angiosome was lost in both the arterial and venous ligation groups. 10 Their findings raise 2 important observations. First, the 2-territory flap is expected to survive based on a single pedicle.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…During the ischemic period several changes take an effect on the skin flap, such as endothelial damage, capillary thrombosis, among others 2,29,32,33 . All can affect the wound healing of the flap.…”
Section: ■ Discussionmentioning
confidence: 99%